1991
DOI: 10.1017/s0022215100116251
|View full text |Cite
|
Sign up to set email alerts
|

Peritonsillar abscess: Risk of disease in the remaining tonsil after unilateral tonsillectomy à chaud

Abstract: The occurrence of disease in the remaining tonsil after unilateral tonsillectomy à chaudin the treatment of peritonsillar abscess, was studied in 536 patients. No patient had a history of previous severe tonsillitis at the time of the unilateral tonsillectomy, 6.1 per cent of the patients were readmitted for surgery of the remaining tonsil during the follow-up period. Ninety-seven per cent of these patients were younger than 30 years of age. Previous investigations have shown increasing frequency by age of pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Sorensen et al [20] studied [20]. The microbiological findings were similar to those from previous reports on peritonsillar abscess [3,6,8,9].…”
Section: Discussionsupporting
confidence: 78%
“…Sorensen et al [20] studied [20]. The microbiological findings were similar to those from previous reports on peritonsillar abscess [3,6,8,9].…”
Section: Discussionsupporting
confidence: 78%
“…Sørensen et al 21 demonstrated that the recurrence rate of PTA and acute tonsillitis in the remaining tonsil was not increased after unilateral tonsillectomy for PTA in patients older than 30 years. Similar results were demonstrated by Christensen and Schønsted‐Madsen 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Among those 42 publications, there were only 5 level I trials [263], [304], [345], [363], [364], the remainder were classified as level IV including 13 case series with only one treatment modality [301], [302], [303], [305], [314], [343], [358], [374], [375], [376], [377], [378], [379], 12 case series comparing different therapies [261], [264], [307], [308], [366], [380], [381], [382], [383], [384], [385], [386], and one economic analysis [301]. Concerning recurrence rates and indication, the authors found 2 level II studies [309], [313] and 13 level IV trials [301], [303], [310], [311], [312], [314], [343], [350], [361], [372], [387], [388], [389]. From the 5 randomized trials, 3 compared the outcome after NA vs. ID in cohorts of 5 [304], 60 [363], and 62 patients [345] and could not reveal a significant difference.…”
Section: Resultsmentioning
confidence: 99%